Multilateral negotiations over climate change policy - Pinto, Lígia (2000)
Negotiations in the real world have many features which tend to be ignored in policy modeling. They are often multilateral, involving many negotiating parties with preferences over outcomes that can differ substantially. They are also often multidimensional, in the sense that several policies are negotiated over simultaneously. Trade negotiations are a prime example, as are negotiations over environmental policies to abate carbon dioxide. We demonstrate how one can formally model this type of negotiation process. We use a policy-oriented computable general equilibrium model to generate preference functions which are then used in a formal multilateral bargaining game. The case study is to climate change policy, but the main contribution is to demonstrate how one can integrate formal economic models of the impacts of policies with formal bargaining models of the negotiations over those policies.